Debt Maturity and the Use of Short-Term Debt : Evidence form Sovereigns and Firms - Chen, Sophia (Departmental Papers; Departmental Paper, 2019)
The maturity structure of debt can have financial and real consequences. Short-term debt exposes borrowers to rollover risk (where the terms of financing are renegotiated to the detriment of the borrower) and is associated with financial crises. Moreover, debt maturity can have an impact on the ability of firms to undertake long-term productive investments and, as a result, affect economic activity. The aim of this paper is to examine the evolution and determinants of debt maturity and to characterize differences across countries.